2012
DOI: 10.1111/j.1365-2788.2012.01645.x
|View full text |Cite
|
Sign up to set email alerts
|

How do static and dynamic risk factors work together to predict violent behaviour among offenders with an intellectual disability?

Abstract: Dynamic and static risk factors appear to capture elements of the same underlying risk associated with violent behaviour in individuals with an ID. This is the first study to empirically explore risk interrelationships in the forensic ID field. We discuss the importance of the contribution of dynamic variables in the prediction and management of risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 35 publications
(95 reference statements)
4
13
0
Order By: Relevance
“…A number of H10 subscale items significantly predicted inpatient aggression in the ID group but not in the comparison group; further, these items had some of the larger effect sizes in our study. This finding suggests greater heterogeneity in the ID group for these items as they rarely are strong predictors of inpatient aggression in non-ID samples (O'Shea et al 2013) and may provide some tentative support to the idea that static items exceed the predictive ability of dynamic items in this population (Lofthouse et al 2014), depending on the items in question. Previous violence (H10.1) was an important predictor of inpatient aggression suggesting that there is a subgroup of ID patients in secure care that are non-aggressive both prior to and during admission.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…A number of H10 subscale items significantly predicted inpatient aggression in the ID group but not in the comparison group; further, these items had some of the larger effect sizes in our study. This finding suggests greater heterogeneity in the ID group for these items as they rarely are strong predictors of inpatient aggression in non-ID samples (O'Shea et al 2013) and may provide some tentative support to the idea that static items exceed the predictive ability of dynamic items in this population (Lofthouse et al 2014), depending on the items in question. Previous violence (H10.1) was an important predictor of inpatient aggression suggesting that there is a subgroup of ID patients in secure care that are non-aggressive both prior to and during admission.…”
Section: Discussionmentioning
confidence: 75%
“…); however, it contrasts with recent research suggesting that static measures have dominance over dynamic measures in predicting violent outcomes among offenders with ID (Lofthouse et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In recent years there has been an increase in research activity and output relating to risk assessment in ID populations (Boer et al, 2004;Gray et al, 2007;Lindsay, 2011;Lindsay et al, , 2006Lindsay et al, , 2008Lofthouse et al, 2013Lofthouse et al, , 2014McGrath et al, 2007;McMillan et al, 2004, Morrisey et al, 2007Quinsey, 2004;Quinsey et al, 2004;Tengströ m et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Lofthous et al . () conducted an interesting analysis where they found that dynamic risk predictors may be act as a proxy for underlying static risk predictors. Lindsay et al .…”
Section: Introductionmentioning
confidence: 99%